Modified Gellan Gum hydrogels with tunable physical and mechanical properties - Coutinho, Daniela F. (2010)
Gellan Gum (GG) has been recently proposed for tissue engineering applications. GG hydrogels are produced by physical crosslinking methods induced by temperature variation or by the presence of divalent cations. However, physical crosslinking methods may yield hydrogels that become weaker in physiological conditions due to the exchange of divalent cations by monovalent ones. Hence, this work presents a new class of GG hydrogels crosslinkable by both physical and chemical mechanisms. Methacrylate groups were incorporated in the GG chain, leading to the production of a methacrylated Gellan Gum (MeGG) hydrogel with highly tunable physical and mechanical properties. The chemical modification was confirmed by proton nuclear magnetic resonance (1H NMR) and Fourier transform infrared spectroscopy (FTIR-ATR). The mechanical properties of the developed hydrogel networks, with Young's modulus values between 0.15 and 148 kPa, showed to be tuned by the different crosslinking mechanisms used. The in vitro swelling kinetics and hydrolytic degradation rate were dependent on the crosslinking mechanisms used to form the hydrogels. Three-dimensional (3D) encapsulation of NIH-3T3 fibroblast cells in MeGG networks demonstrated in vitro biocompatibility confirmed by high cell survival. Given the highly tunable mechanical and degradation properties of MeGG, it may be applicable for a wide range of tissue engineering approaches.